Analisis Kemampuan Berfikir Kritis Siswa Menggunakan Teams Assisted Individualization (Pembelajaran Sains Materi Gerak) - Ahmad Khoiri (Universitas Muhammadiyah Sidoarjo, 2017)
The aims of the Research are to difference of learning result and ability of critical thinking before and after treatment (treatment). Methods used with pretest and posttest for learning outcomes; questionnaires for students' critical thinking skills. Data analysis technique used reliability test, normality test, homogeneity test and hypothesis test of t one party test. The result of data analysis shows: 1) Based on pre test result, initial condition of student before using cooperative learning model type Teams Assisted Individualization experimental class 74,9 and control class 75,3 medium category. 2) end ability test to train students critical thinking ability show result tcount> ttable or 3,934> 1,684 (significance level 5%) means there is influence of cooperative learning model type Teams Assisted Individualization. 3) There is difference of critical thinking ability of class VIIA student with VIIB Junior High School Ma'arif Mlandi for 77 for experiment class and 75 control class and critical thinking ability equal to 79,6 with high category. 4) There was an increase in learning outcomes before and after the treatment of cooperative learning model type Teams Assisted Individualization of 74.9 to 77